Cyprian and Roman Carthage. - Brent, Allen (Cambridge Cambridge University Press, 2010)
"Thascius Caecilius Cyprianus believed fervently that his conversion experience had been a passage from the darkness of the world of Graeco-Roman paganism to his new vision of Christianity. But Cyprian's response as bishop to the Decian persecution was to be informed by the pagan culture that he had rejected so completely. His view of church order also owed much to Roman jurisprudential principles of legitimate authority exercised within a sacred boundary spatially and geographically defined. Given the highly fragmented state of the non-Christian sources for this period, Cyprian is often the only really contemporary primary source for the events through which he lived. In this book, Allen Brent contributes to our understanding both of Roman history in the mid-third century and of the enduring model of church order that developed in that period"--Provided by publisher.
1. Cyprian's life and controversies -- 2. Cyprian's background in Roman Carthage -- 3. Historiography in the age of Decius -- 4. Decius' religious policy and political rhetoric -- 5. The Decian persecution -- 6. The church of the martyrs -- 7. Stephen's challenge to the sacramentum unitatis -- 8. A final postscript : Cyprian's legacy.
Keywords: Cyprian, -- Saint, Bishop of Carthage; Church discipline; Church history -- Primitive and early church, ca. 30-600; Church polity; 276 =71 CYPRIANUS, THASCIUS CAECILIUS -- Latijnse patrologie--CYPRIANUS, THASCIUS CAECILIUS; Carthage (Extinct city) -- Church history